PENGARUH FAKTOR GEOGRAFIS, DEMOGRAFIS DAN PSIKOGRAFIS PADA PEMASARAN REALESTAT BERKONSEP MINIMALIS DI SURABAYA - Sofia Hendrastuti; Christiono Utomo (Jurnal Teknobisnis, 2006)
In the beginning of 2005, property business in Surabaya went into a new decade by the emergence of the new set of trend in housing/real estate, which is often called as 'minimalist architecture'. Thosewho apply the system of multi-concepts, would have no difficulties in marketing their products. To those developed minimalist architectures showed that developers chose the system of single-concept could not fulfill their targets of marketing. Thus we could consider this as an indicator of certain formula, that is: what kind of factors that would be considered by customers-to-be before buying 'minimalist-housing'? and how was the character of those costumers- to-be in its relations with geographic, demographic, and psychographic aspects?. The sampling techniques used "random sampling', which was applied to half part of "minimalist-concepts-housing" using the system of single-concept customers in Surabaya, as the population. Data was analysis using "exploratory factor analysis '. Comparison between variables was tested using t-test, Mann maitney, Anova, and Kruskall Wallis techniques. This research resulted in there were 4 factors which would be taken into consideration by the customers-to-be in buying minimalis-concepts-housing'. These factors were: material, design, model and color. It was also found out that those costumers-to-be in Surabaya, had different characters according togeographic, demographic and psychographic aspects.